Ignition of Free Gas in the Peritoneal Cavity: An Explosive Complication. (29th January 2013) - Mumith, Aadil; Thuraisingham, Justin; Gurunathan-Mani, Sivaraman
Abstract : We report an extremely rare event where the use of diathermy to enter the peritoneal cavity caused the free gas within it to ignite and consequently burn the surgeon during a standard right hemicolectomy procedure for a caecal perforation. This should be noted as a possible safety concern intraoperatively. We conclude that sharp dissection should always be used initially when entering the peritoneal cavity where free gas is present, cautery can subsequently be used once the free air has escaped.